APLIKASI RUANG GURU UNTUK PEMBELAJARAN DI ERA COVID-19 - Suriani, Irda; Marini, Yushita; Marina, Nisha; Nasution, Muhammad Muslim; Lubis, Maulana Arafat (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThe COVID-19 era requires the world of education to transform its learning system towards application-based digitalization. The current learning application that is widely discussed is Ruangguru. Ruangguru is an application that is intended to help students learn because the content is based on subjects by the curriculum in Indonesia. This study aims to explore the effectiveness of the Ruangguru application for learning, especially in the scope of elementary schools. This research method is descriptive quantitative through the survey. The population of this study were elementary/MI students in the city of Padangsidimpuan, North Sumatra. The sampling technique used in this study is probability sampling which includes simple random sampling, so the number of students who respond is 81 people. Data collection techniques using a Google Form-assisted questionnaire. Analysis of research data using descriptive statistics assisted by STATCAL software. The results of this study found data that the Ruangguru application seemed to be effectively used for learning for SD/MI students in the Padangsidimpuan City area of North Sumatra Province during the COVID-19 pandemic with an average percentage of 80.25%. Keywords: Ruangguru application; Learning; COVID-19 AbstrakEra COVID-19 menuntut dunia pendidikan bertransformasi sistem pembelajarannya menuju digitalisasi berbasis aplikasi. Aplikasi pembelajaran saat ini yang banyak diperbincangkan ialah Ruangguru. Ruangguru adalah aplikasi yang diperuntukkan membantu siswa dalam belajarnya karena isinya berdasarkan mata pelajaran yang sesuai kurikulum di Indonesia. Penelitian ini bertujuan untuk menelusuri keefektifan aplikasi Ruangguru untuk pembelajaran khususnya di lingkup sekolah dasar. Metode penelitian ini adalah kuantitatif deskriptif melalui survei. Populasi penelitian ini adalah siswa SD/MI yang berada di wilayah Kota Padangsidimpuan, Sumatera Utara. Teknik sampelyang digunakan dalam penelitian ini ialah probability sampling yang meliputi simple random sampling, jadi siswa yang merespon berjumlah 81 orang. Teknik pengumpulan data menggunakan kuesioner berbantuan Google Form. Analisis data penelitian memakai statistik deskriptif berbantuan software STATCAL. Hasil penelitian ini menemukan data bahwa aplikasi Ruangguru terlihat efektif digunakan untuk pembelajaran bagi siswa SD/MI di wilayah Kota Padangsidimpuan Provinsi Sumatera Utara selama masa pandemi COVID-19 dengan memiliki rata-rata persentase 80,25%. Kata kunci: Aplikasi Ruangguru; Pembelajaran; COVID-19